Climate Risk Management in Agricultural Extension (CRMAE) Refresher Training - Grossi, Amanda; Dinku, Tufa; Hansen, James; Trzaska, Sylwia; Nsengiyumva, Gloriose (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A six-day refresher training of trainers (ToT) workshop was implemented from March 7-12, 2022, in Bishoftu, Ethiopia by the International Research Institute for Climate and Society (IRI) of the Columbia Climate School. The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project and in close collaboration with the Adapting Agriculture to Climate Today, for Tomorrow (ACToday) Columbia World Project, brought together various professionals from the Ministry of Agriculture (MoA), Agricultural Technical and Vocational Education and Training (ATVET) colleges, the Ethiopian Institute of Agricultural Research (EIAR), and the Ethiopian Meteorological Institute (NMI) to provide final input and feedback for the Climate Risk Management in Agricultural Extension (CRMAE) curriculum and its associated teaching and learning materials.